Edukasi Anemia pada Ibu Hamil di Puskesmas Cipondoh, Kota Tangerang - Novfrida, Yizri; Pusmaika, Rangga (Jurnal ABDIMAS-HIP Pengabdian Kepada Masyarakat, 2024)
Globally, pregnant women are the population group most vulnerable to anemia. In 2019, the prevalence of pregnant women with anemia worldwide reached 37%. Word Bank Development Data, shows that Indonesia is one of the countries that has experienced an increase in the prevalence of pregnant women with anemia every year since 2010 by 40% to 44% in 2019. This condition of the high prevalence of anemia in pregnant women requires special attention from various parties, because iron anemia in pregnancy increases the risk of maternal death due to postpartum hemorrhage. The aim of this community service activity is to increase knowledge about preventing anemia in pregnant women at the Cipondoh Community Health Center. The activity was carried out on Thursday 14 March 2024, at the Cipondoh Community Health Center, Tangerang City, which was attended by 15 pregnant women in the second and third trimesters. The method used was counseling and questions and answers using flip-sheet leaflets about anemia in pregnancy. After the counseling is carried out, participants can understand about anemia in pregnant women, its causes, impacts and how to prevent it. Educational activities to prevent anemia for pregnant women need to continue to be carried out to increase knowledge and pay special attention to health problems during pregnancy.